ONE-STAGE SUBTOTAL ESOPHAGECTOMY AND RIGHT UPPER LOBECTOMY WITH RESECTION OF MAIN AND INTERMEDIATE BRONCHI IN SYNCHRONOUS ESOPHAGEAL AND LUNG CANCER - A. B. Ryabov; V. V. Cheremisov; N. М. Khomyakov; О. V. Pikin; М. М. Shemetova; L. V. Telegina; N. N. Bolchenko; I. V. Kolobaev; A. V. Chaika; А. К. Kostrygin (Сибирский онкологический журнал)
We report a rare case of successful surgical management (simultaneous esophagectomy and upper lobectomy with resection of the main and intermediate bronchi) of synchronous multiple primary cancer of the thoracic esophagus and central cancer of the right lung.    The role of morphological characteristics in differential diagnosis between synchronous neoplasia and metastasis has been described. This clinical case demonstrates successful one-stage surgical management of this disease provided a correct assessment of the extent of cancer involvement and the patient’s functional status.